RESONANCES IN SATURN’S SYSTEM - Voitko, A. S.; Troianskyi, V. V. (Одеські астрономічні публікації, 2017)
One of principal tasks of celestial mechanics is study of motion of natural satellites of planets. In this work, the authors have examined resonances in system of satellites and rings of Saturn. They have showed presence of resonances between all the regular satellites and satellites – rings.